SLOPE STABILITY COEFFICIENT CALCULATION OF THE KOK-TOBE MOUNT WITH CONSIDERING SEISMIC ACTIVITY USING GEO5 PROGRAM (Journal of Geography and Environmental Management, 2022)
Modern dangerous signs are manifested in the nature of the most significant components of engineering and geological conditions, ensured by the safety of people's life, the features of industrial and abrupt construction in mountainous and foothill areas, and, consequently, in conditions of sustainable economic development. In the event of serious development processes, serious difficulties arise for the construction and use of various engineering measures that require ensuring the safety of the population and taking measures to prevent and protect the population. During the design of anti-landslide measures, when erecting structures on unstable slopes or when distributing mechanisms on slopes and sides of ravines, works must begin with assessment stability degree of the inclined earth surface. Such assessment is made by calculating the slope stability coefficient, which is characterized by the ratio of the holding forces to the shear forces of the soil mass on an inclined surface. The paper presents the results of research in Almaty city on the experimental site on the slope of mountain Kok-Tobe. The article presents calculations of slope stability coefficient in "GEO5" program, in the natural state and taking into account seismic impact. As result of the calculation, unfavorable factors and risks in terms of slope stability are identified and recommended measures are also given.
Keywords: Hazardous geological processes, urban territory, landslide, slope stability coefficient.